THE EFFECT OF PERSONAL SELLING AND SERVICE QUALITY ON CUSTOMER LOYALTY AT PT. WANRIAU INDOXP - Astri Ayu Purwati; Kristin Rukmana; Mazzlida Matt Deli (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
The service sector is developing rapidly, one of such service sectors is internet provider. This study aims to determine the effect of personal selling and service quality on customer loyalty at PT. WanRiau IndoXP Pekanbaru. The samples of this study were 146 respondents who were customers of PT. WanRiau IndoXP. Data analysis used is multiple linear regression through t-test for testing the hypothesis. The conclusions that can be drawn from the results of research include: (1) Personal Selling has a significant effect on customer loyalty 2) Tangible has a significant influence on customer loyalty. The company must increase the number of facilities and provide employee training so that more leverage in working. (3) Reliability has a significant effect on customer loyalty (4) Responsiveness has a significant effect on customer loyalty (5) Emphaty has a significant influence on customer loyalty (6) Assurance based has a significant effect on customer loyalty. Customers feel comfortable when making transactions and interact in PT. Wanriau IndoXP (PERSERO) Pekanbaru.